2009
DOI: 10.1017/s0007114509992273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organically and conventionally produced diets on jejunal gene expression in chickens

Abstract: Using a nutrigenomics approach we studied the response of second-generation chickens at a transcriptional level to organically grown feed ingredients compared with conventionally grown feed ingredients. Both diets consisted of the same amounts of ingredients, the only difference was the production method. Gene expression was analysed in jejuni using whole genome chicken cDNA arrays. After analysis, forty-nine genes were found to be differentially regulated between chickens fed on the different diets, independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…However, it cannot be excluded that a small compositional difference can bring about health effects in humans. In an intervention study in chickens,9 even small differences in diet composition were shown to have an effect on some immune parameters and on genetic expression 10. This may also apply to humans.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, it cannot be excluded that a small compositional difference can bring about health effects in humans. In an intervention study in chickens,9 even small differences in diet composition were shown to have an effect on some immune parameters and on genetic expression 10. This may also apply to humans.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, it is difficult to determine the health relevance based purely on nutritional content. A Dutch intervention study in chickens showed that birds fed either an organic or a conventional diet showed differences in growth9 and jejunum gene expression 10. However, the caloric content of the diets was comparable and only minor differences in nutritive components existed 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Even when diets are quite similar, differences between GIT microbiota may still be observed. For example, when de Greeff et al (62) compared jejunal gene expression in layer hens fed either conventional or organic diets of an otherwise identical composition, they detected differences in the expression of 49 genes, including those associated with cholesterol synthesis and immunological processes. In addition, pasture flock birds have access to a much wider variety of food sources such as insects and forages in addition to the formulated diets provided.…”
Section: Potential Factors That Influence Git Microbiomes In Pasture mentioning
confidence: 99%
“…Os nutrientes podem estimular ou reprimir expressões gênicas (Rodriguez, 2010), nesse contexto, hipóteses de que componentes dietéticos da cevada ou a própria fibra possa ter influenciado genes relacionados ao crescimento do órgão não podem ser descartadas. Greeff et al (2009) ABSTRACT: Crassostrea gigas is considered the most cultivated species in the world, due to its good adaptation to climatic and geological conditions. The composition of its shell is basically calcium carbonate.…”
Section: Resultsunclassified